Cyp1B1 expression promotes angiogenesis by suppressing NF-κB activity - Palenski, Tammy L. (American Physiological Society, 2013)
Nuclear factor-κB (NF-κB) is a master regulator of genes that control a large number of cellular processes, including angiogenesis and inflammation. We recently demonstrated that cytochrome P-450 1B1 (Cyp1B1) deficiency in endothelial cells (EC) and pericytes (PC) results in increased oxidative stress, alterations in migration, attenuation of capillary morphogenesis, sustained activation of NF-κB, and increased expression of thrombospondin-2 (TSP2), an endogenous inhibitor of angiogenesis. On the basis of a growing body of evidence that phenethyl isothiocyanate (PEITC) and pyrrolidine dithiocarbamate (PDTC) function as antioxidants and suppressors of NF-κB activation, we investigated their potential ability to restore a normal phenotype in Cyp1B1-deficient (cyp1b1(−/−)) vascular cells. PEITC and PDTC inhibited NF-κB activity and expression in cyp1b1(−/−) EC and PC. We also observed restoration of migration and capillary morphogenesis of cyp1b1(−/−) EC and decreased cellular oxidative stress in cyp1b1(−/−) EC and PC without restoration to normal TSP2 levels. In addition, expression of a dominant-negative inhibitor κBα, a suppressor of NF-κB activation, decreased NF-κB activity without affecting TSP2 expression in these cells. In contrast, knockdown of TSP2 expression resulted in attenuation of NF-κB activity in cyp1b1(−/−) vascular cells. Furthermore, expression of TSP2 in wild-type (cyp1b1(+/+)) cells resulted in increased NF-κB activity. Together, our results demonstrate an important role for TSP2 in modulation of NF-κB activity and attenuation of angiogenesis. Thus Cyp1B1 expression in vascular cells plays an important role in the regulation of vascular homeostasis through modulation of the cellular reductive state, TSP2 expression, and NF-κB activation.